(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Total war continues to be a topic of debate and research in modern conflicts. Technological inventions and the interconnectedness of the global community amplify the effect of the consequences of warfare. We reexamine the totality of modern armed conflicts through an analysis of the achievement and level of destruction that pose new ethical, legal and political challenges. The author answers the questions about: the deep psychological and political implications that extend beyond the battlefield that transmit in depth and encompass the entire (global) society. We define total war through the criteria of: intentional targeting of civilians, civilian resources and infrastructure and the firm control of the population’s behavior through the installation of fear, hatred and trauma; through the political attempt through the war to gain and consolidate support among the people, entailing debates about civil liberties and erosion of democratic principles; the treatment of prisoners and the mass executions of the adversary as well as our own insufficiently motivated forces and ideologically unfit population; and a possible cataclysmic scenario of the use of atomic weapons. The analysis emphasizes the complex roles of traditionally non-combatant categories and new technologies and doctrines and their impact on the totality of warfare. The position remains that total war is an ideal concept, but also the unanswered question if there are atypicalities of that concept, which is the deviation from the benchmark for how limited the war and its constituent elements are instead of total. The research concludes that total war changes cultures, geopolitical views and international relations, and that its legacy changes the course of history for generations to come.